Level Control System Using Differential Pressure Transmitter For CPO Holding Tanks - Mansyur, Mansyur; Hanief, Said; Yunianto, Yunianto (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2023)
The use of instruments at this time is very much needed, especially in industry. One example of an instrument is a transmitter, where the transmitter consists of an electrical transmitter. The transmitter is a device used to convert physical signals into instrument signals or send signals from the transmitter (sensor) to the controller and from the controller to the final controller. In this case, we will discuss the measurement of CPO liquid level, where what is measured is the height of CPO liquid using an electric differential pressure transmitter, which is equipped with other instrumentation equipment such as recorders, transmitters, digital manometers, DC voltage sources, pressure gages, compressors, air regulators. . From level measurement using an electric differential pressure transmitter, the results of the level measurement are proportional to the physical pressure, where the 6000 mm tank level has an instrument signal of 20 mA. The 0 mm tank level has an instrument signal of 4 mA.